Embryonal rhabdomyosarcoma of urinary bladder in an adult patient: an unusual manifestation. (13th April 2018) - Aggarwal, Ajay; Singh, Vishwajeet; Pandey, Siddharth; Sinha, Rahul Janak
Abstract : An adult man presented with off and on painless haematuria, which was diagnosed as bladder mass on contrast-enhanced CT. He underwent transurethral resection of bladder tumour with complete resection. A diagnosis of embryonal rhabdomyosarcoma was made following histopathology and immunohistochemistry report. The patient was planned for radical cystectomy but was found to have large recurrent infiltrating bladder mass with liver and bone metastasis. Hence, the plan for radical cystectomy was deferred and the patient was counselled regarding chemotherapy (vincristine, cisplatin and doxorubicin regime). The patient tolerated the first cycle of chemotherapy, but his condition deteriorated prior to the second cycle and the patient expired.